Case Report: A case of complete response to entrectinib in NTRK fusion gene-positive parotid gland cancer - Moriyama, Etsuko; Nagasu, Sachiko; Tanaka, Toshimitsu; Shimotsuura, Yasutaka; Ono, Takeharu; Umeno, Hirohito; Akiba, Jun; Kawahara, Akihiko; Fujita, Fumihiko; Kawaguchi, Takumi; Miwa, Keisuke (Frontiers in Oncology, 2023)
Introduction: Expression of the NTRK gene is rare in solid tumors but is highly prevalent in salivary gland secretory carcinomas. Here, we report a case of a complete response to entrectinib in a patient with NTRK fusion gene-positive parotid carcinoma. Case description: The patient was a 44-year-old man who underwent total left parotidectomy and left cervical lymph node dissection for a left parotid tumor at 24 years of age. The histopathological diagnosis was mammary analog secretory carcinoma. Postoperatively, the patient received only radiation therapy. Sixteen years after the surgery, the patient became aware of a mass in the left parotid region. A close examination revealed local recurrence and multiple cervical lymph node metastases. S-1 monotherapy was started as chemotherapy but was discontinued 3 years later because of disease progression. As there was no standard treatment, a comprehensive genomic profiling test using a next-generation sequencer was performed, and the ETV6-NTRK3 fusion gene was identified. Entrectinib, an NTRK inhibitor, was immediately administered at a dose of 600 mg/day. The local recurrence rapidly shrank grossly from the beginning of treatment, and a complete response was observed 6 months later. However, creatinine levels exhibited an increase at week 68 of treatment; consequently, entrectinib dosage was lowered to 400 mg/day, leading to an immediate improvement in creatinine levels. Entrectinib was associated with additional side effects, including dysgeusia, fatigue, dizziness, and weight gain, all of which were also alleviated by the reduction in entrectinib dose. Thirty months after treatment initiation, the patient maintained a complete response and continued to receive entrectinib. Conclusion: The NTRK fusion gene should always be checked in the presence of salivary gland secretory carcinoma.